Parental Gender Affirmation Model: A culturally informed framework - Stanley R. Vance, Jr; Luz Venegas; Jack Johnson; Anita V. Chaphekar; Anoushka Sinha; Deepika D. Parmar; Jae Sevelius (Elsevier, 2024)
Benefits of parental gender-affirming behaviors on the mental health and well-being of the broader gender-expansive youth population have been extensively documented. However, the nature and impact of these behaviors have not been explored by centering Black and Latine transgender/non-binary youth (BLTY). This article offers a new framework called the "Parental Gender Affirmation Model." This framework conceptualizes parental gender-affirming behaviors toward BLTY through the lenses of intersectional stigma and cultural gender norms and uses the Theory of Planned Behavior and Modified Gender Affirmation Model as foundational frameworks. We analyzed qualitative data from 43 interviews with BLTY, parents of BLTY, and Black and Latine transgender/non-binary young adults from California in the United States to develop the framework. The "Parental Gender Affirmation Model" starts with behavioral antecedents and ends with impacts of these behaviors on BLTY's well-being. This framework will inform the development of critically needed, culturally-informed interventions to support parental gender affirmation of BLTY.